2019
DOI: 10.1016/j.celrep.2019.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Molecular Basis for Katanin-Mediated Severing of Glutamylated Microtubules

Abstract: Highlights d Structures of the apo and ATPgS-bound AAA domain of katanin p60 are determined d The YRG motif of pore loop 1, unique to katanin, is crucial for katanin activity d Katanin remodels glutamylated microtubules and controls axon growth d Katanin and spastin recognize and remodel microtubules in distinct ways

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 63 publications
(94 reference statements)
4
57
0
Order By: Relevance
“…concentrated Camsaps into the central lumen, where Camsaps stabilized the minus ends of the seeds to allow central MT elongation. As emerging evidence suggests that Wdr47, Camsaps, and Katanin also similarly impact neuronal polarization and axonal growth 14,15,17,40,41 , our findings indicate that the same pathway is used to properly generate and organize non-centrosomal MT arrays in polarized subcellular compartments such as the axon and motile cilium.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…concentrated Camsaps into the central lumen, where Camsaps stabilized the minus ends of the seeds to allow central MT elongation. As emerging evidence suggests that Wdr47, Camsaps, and Katanin also similarly impact neuronal polarization and axonal growth 14,15,17,40,41 , our findings indicate that the same pathway is used to properly generate and organize non-centrosomal MT arrays in polarized subcellular compartments such as the axon and motile cilium.…”
Section: Introductionsupporting
confidence: 59%
“…Nevertheless, no evidence to date suggests a localization of -tubulin in mammalian multicilia [61][62][63] . As Katanin is able to server curved MT lattices and MTs that are post-translationally modified (including poly-glutamylation abundant in peripheral MTs) 37,40,64,65 , we propose that it directly servers peripheral MTs to generate the seeds (Fig. 7g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tant for regulation of microtubule turnover and the recruitment of microtubule severing enzymes, such as katanin and spastin (16)(17)(18). Glycylation is primarily found on cilia, but the functional role of polyglycylation is not well-understood (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that polyglutamylation induces microtubule severing by recruiting and honing katanin and spastin severing protein activity. [58][59][60] Additionally, paclitaxel treatment increases tubulin polyglutamylation within microtubules and we hypothesized that the increased polyglutamylation could sensitize microtubules to severing by spastin. 61 In a preliminary experiment, we measured the levels of tubulin polyglutamylation over time in synchronized A549 cells after release from a G1/S block.…”
Section: Discussionmentioning
confidence: 99%